2017
DOI: 10.1007/s11739-017-1627-7
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of procalcitonin in differentiating Candida and bacterial blood stream infections in critically ill septic patients outside the intensive care unit

Abstract: We aimed to explore the role of procalcitonin (PCT) for the diagnosis of Candida spp. bloodstream infections in a population of critically ill septic patients admitted to internal medicine units. This is a retrospective case-control study considering all cases of candidemia identified in three internal medicine units, from January 1st 2012 to May 31st 2016. For each case of candidemia, two patients with bacteremic sepsis were included in the study as control cases. The end point of the study was to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Our study confirmed that the PCT median value of bacteremia patients with Gramnegative bacteria infection was significantly higher than that of Gram-positive bacteria infection. These findings are consistent with the previously published literature (1,10,11). But because the specificity was only 27%, the 0.581 of area under the curve was unsatisfactory and could not guide clinical diagnosis and treatment, which was in consistent with conclusions from Thomas-Rüddel et al (13).…”
Section: Microorganismssupporting
confidence: 92%
See 1 more Smart Citation
“…Our study confirmed that the PCT median value of bacteremia patients with Gramnegative bacteria infection was significantly higher than that of Gram-positive bacteria infection. These findings are consistent with the previously published literature (1,10,11). But because the specificity was only 27%, the 0.581 of area under the curve was unsatisfactory and could not guide clinical diagnosis and treatment, which was in consistent with conclusions from Thomas-Rüddel et al (13).…”
Section: Microorganismssupporting
confidence: 92%
“…Recent studies showed that PCT was a promising inflammatory marker, which can distinguish systemic bacterial infection from other types of infections, judge the severity of bacterial infection, estimate the therapeutic effect and prognosis of BSI, and guide the use of antibiotics (6)(7)(8)(9). Some recent studies have further found that PCT can distinguish different types of pathogenic bacteria on the basis of Gram staining in patients with BSI (1,10,11), providing rapid support for the preliminary selection of antibiotics. However, other studies did not show these findings (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…However, different real-life experiences in patients with intra-abdominal infection and in ICU patients with bloodstream infection suggest that higher cutoff should be considered in these settings [32,37]. In this latter case, higher cutoff values may be helpful to differentiate between bacterial and fungal infections [46,47]. It is worth noting that all the available literature was produced using the high sensitive assays based on B…”
Section: Discussionmentioning
confidence: 99%
“…Although there is little evidence, it appears that PCT minimally increases in the presence of fungal infection. 27 …”
Section: Discussionmentioning
confidence: 99%